2018
DOI: 10.4064/ap170823-23-1
|View full text |Cite
|
Sign up to set email alerts
|

New regularity criteria for the 3D Hall-MHD equations

Abstract: Abstract. We prove some regularity criteria for smooth solutions of the three-dimensional incompressible Hall-magnetohydrodynamic equations involving only two components of the velocity and magnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Hassan et al [11] explored the properties of the wall in a porous channel, for the peristaltic flow of MHD nanofluid. Alghamdi et al [12] demonstrated the smooth solutions for three-dimensional Hall-MHD equations through regularity criteria. Ahmed et al [13] discussed the generalized time-convection of non-local nanofluids in a vertical channel.…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al [11] explored the properties of the wall in a porous channel, for the peristaltic flow of MHD nanofluid. Alghamdi et al [12] demonstrated the smooth solutions for three-dimensional Hall-MHD equations through regularity criteria. Ahmed et al [13] discussed the generalized time-convection of non-local nanofluids in a vertical channel.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical modelling of systems and processes has had a growing development in fields as physics, chemistry, aerodynamics, electro-dynamics of complex medium, polymer rheology (see e.g. [4], [18], [19]). In fact, the subject of fractional differential equations has been gaining more importance and attention in ordinary and partial differential equations involving both Riemann-Liouville and Caputo fractional derivatives.…”
Section: Introductionmentioning
confidence: 99%